2006
DOI: 10.1093/jnci/djj129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prostate-Specific Antigen Declines for Surrogacy in Patients Treated on SWOG 99-16

Abstract: Several PSA measures satisfied the surrogacy criteria for survival in a retrospective analysis of data from SWOG 99-16. However, these measures await prospective validation in future clinical trials of chemotherapy in men with androgen-independent prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
175
4
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(189 citation statements)
references
References 14 publications
5
175
4
5
Order By: Relevance
“…Notably, our findings are similar to previously published results of the TAX327 and SWOG 99-06 studies in which PSA decline of 30% within 3 months of treatment initiation provided surrogacy for OS. 10,11 The presented 30% cutoff had a higher degree of statistical surrogacy than traditional 50% cutoff by using the most stringent surrogacy criterion, the proportion of treatment effect explained (PTE) in SWOG 99-06. 12 In this study, we found that 13% of men with CRPC had biopsy Gleason 6 disease at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our findings are similar to previously published results of the TAX327 and SWOG 99-06 studies in which PSA decline of 30% within 3 months of treatment initiation provided surrogacy for OS. 10,11 The presented 30% cutoff had a higher degree of statistical surrogacy than traditional 50% cutoff by using the most stringent surrogacy criterion, the proportion of treatment effect explained (PTE) in SWOG 99-06. 12 In this study, we found that 13% of men with CRPC had biopsy Gleason 6 disease at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the changes of PSA concentrations in patients treated with hormonal therapy may be associated with the reduction of tumor mass with different kinetics compared to cytotoxic chemotherapy. Despite the fact that the decrease of PSA concentration is usually less dramatic after cytotoxic chemotherapy compared to hormonal treatment, the change of PSA concentration is an established surrogate endpoint in patients with castration-resistant prostate cancer treated with docetaxel (10) . However, the daily clinical practice has taught us that the changes of serum PSA concentrations must be interpreted with caution as a phenomenon of PSA surge denoting a rise of concentrations with subsequent decline has been described (11,12) .…”
Section: Bohuslav Melicharmentioning
confidence: 99%
“…A pivotal assessment of PSA as a surrogate for OS was performed as part of the Southwest Oncology Group (SWOG) 99-16 study, 6 in which patients with androgen-independent prostate cancer were assigned treatment with docetaxel/estramustine or mitoxantrone/prednisone. The group receiving docetaxel gained a 2-3 month OS benefit.…”
Section: Appraisal Of End Points In Phase II and Iii Trials In Castramentioning
confidence: 99%